Vagus Nerve Stimulation in Neurology and Beyond: A Comprehensive Review of Clinical Use, Mechanisms, Innovations and Future Directions - Janiszewski, Michał; Komorowski, Marcin; Piecek, Joanna; Omiecińska, Marta; Surosz, Natalia; Graczyk, Aleksandra; Grochowalski, Michał; Szydło, Jakub; Ziętara, Dominika; Kmieć, Kacper (Quality in Sport, 2026)
Background: Vagus nerve stimulation (VNS) has evolved from a treatment for drug-resistant epilepsy (DRE) into a broader neuromodulatory platform with expanding applications in neurology, psychiatry, immunology, and cardiology. Technological advances, particularly in non-invasive and adaptive modalities, have renewed interest in its therapeutic potential. Aim: To provide a comprehensive review of the clinical applications, mechanisms of action, safety profile, and emerging technological innovations in VNS, with emphasis on non-invasive techniques, adaptive stimulation, candidate biomarkers, and associated ethical considerations. Material and Methods: This narrative review synthesizes findings from peer-reviewed studies, clinical trials, and experimental reports identified through targeted searches in PubMed, Google Scholar, and related databases. Results: VNS demonstrates consistent efficacy in reducing seizure frequency in epilepsy and improving outcomes in treatment-resistant depression (TRD), inflammatory conditions, and cardiovascular disorders. Mechanistically, it modulates brainstem–cortical circuits, autonomic tone, and neuroimmune signaling pathways. Side effects are typically mild and transient. Non-invasive and closed-loop systems show promise in enhancing individualization and tolerability, although challenges remain in terms of standardization, long-term data, and equitable access. Conclusions: VNS represents a safe, increasingly personalized intervention with broad therapeutic scope. Future research should prioritize biomarker validation, optimization of stimulation paradigms, and integration with artificial intelligence (AI) and digital health tools, ensuring ethical and scalable implementation across diverse clinical populations.